Social Responsibility Code – Instrument for Better Correlation of Policies in the Field of Bio-Economy - Vasile Dinu (Amfiteatru Economic)
The contemporary society focuses on issues such as sustainability, environmental protection, sustainable consumption, promotion of clean technologies, sustainable agriculture, biodiversity conservation, food security, fair employment, fair trade, green biotechnology, expanded use of renewable energy etc. Due to the wide scope and different incentives, sustainable development raises major social, economic and environmental challenges, mainly for companies. At the same time, there is a more acute need for analyzing the stability and prospects of any company, not only in terms of financial indicators, but also in terms of social and environmental performance. In this respect, the enactment of the EU Directive 34/2013 (amended by 95/2014), requiring large companies to disclose nonfinancial information and information on diversity, is significant. Responding to the social interest, even enterprises that are not subject of the Directive compete in disclosing their social responsibility through policies, measures and actions. While, for most organizations, social responsibility has, by definition, a voluntary nature, and the existing regulations are vague, companies tend to publish results that show them in a favorable light and silently pass the negative impact ‒ in some respects ‒ of their work. In order to mitigate the heterogeneity of approaches and to facilitate comparisons, identify best practices, develop rankings and track progress, several codes, "reference frameworks" have been initiated for the integration of social responsibility policies and for reporting achievements on these issues. Among these, United Nations Global Compact, the Global Reporting Initiative, Accountability Framework and ISO 26000 are better known internationally.